Sensory Assessment of Odour Emissions in Wastewater Treatment: Implications for Biosolids Management - Guerrero, Thais N.; Fisher, Ruth M.; Prata, Ademir A. [UNESP]; Stuetz, Richard (My University, 2024)
The beneficial reuse and recovery of biosolids is an attractive option instead of disposal. However, odour emissions present significant challenges to land application of biosolids, increasing operational costs and reducing community acceptance. This study aimed to assess the influence of conveying and storage conditions in wastewater treatment plants on the sensory impact from biosolids. For sensory assessment, samples of anaerobically digested biosolids were collected after centrifuge and during storage out-loading. The emissions were extracted over 15 days using a dynamic flux chamber and sensory analysis conducted using an ODP coupled to a TD-GC-MS. Odour descriptors and intensities (from 1 – weak to 4 – strong) were evaluated by expert panellists, providing insights into the sensory aspects of odour emissions. The ODP results showed variations in the number of occurrences, intensity and modified frequency of odour events across the stages of wastewater solids processing and laboratory storage. Conveying could potentially impact the release of volatile compounds due to the mechanical agitation that can aerate and disturb the structure and surface of the biosolids. On the other hand, storage can accelerate biological and chemical processes as a result of the development of anaerobic conditions leading to subsequent odour generation. The interplay between wastewater treatment processes and odour emissions is complex and requires targeted strategies. The application of sensorial analysis contributes to valuable insights into understanding and managing odour emissions in wastewater treatment plants, offering potential avenues for optimizing operational parameters to benefit biosolids reuse initiatives.
Keywords: Anaerobic digestion; Beneficial reuse; Biosolids; Gaseous emissions; Land application; Odour detection port; Sensory analysis; Sensory emissions; Wastewater sludge